On the paternal origin of trisomy 21 Down syndrome - Hultén, Maj A (BioMed Central, 2010)
BACKGROUND: Down syndrome (DS), characterized by an extra free chromosome 21 is the most common genetic cause for congenital malformations and learning disability. It is well known that the extra chromosome 21 originates from the mother in more than 90% of cases, the incidence increases with maternal age and there is a high recurrence in young women. In a previous report we have presented data to indicate that maternal trisomy 21 (T21) ovarian mosaicism might provide the major causative factor underlying these patterns of DS inheritance. One important outstanding question concerns the reason why the extra chromosome 21 in DS rarely originates from the father, i.e. in less than 10% of T21 DS cases. We here report data indicating that one reason for this parental sex difference is a very much lower degree of fetal testicular in comparison to ovarian T21 mosaicism. RESULTS: We used fluorescence in situ hybridisation (FISH) with two chromosome 21-specific probes to determine the copy number of chromosome 21 in fetal testicular cell nuclei from four male fetuses, following termination of pregnancy for a non-medical/social reason at gestational age 14-19 weeks. The cells studied were selected on the basis of their morphology alone, pending immunological specification of the relevant cell types. We could not detect any indication of testicular T21 mosaicism in any of these four male fetuses, when analysing at least 2000 cells per case (range 2038-3971, total 11.842). This result is highly statistically significant (p < 0.001) in comparison to the average of 0.54% ovarian T21 mosaicism (range 0.20-0.88%) that we identified in eight female fetuses analysing a total of 12.634 cells, as documented in a previous report in this journal. CONCLUSION: Based on these observations we suggest that there is a significant sex difference in degrees of fetal germ line T21 mosaicism. Thus, it would appear that most female fetuses are T21 ovarian mosaics, while in sharp contrast most male fetuses may be either very low grade T21 testicular mosaics or they may be non-mosaics. We further propose that this sex difference in germ line T21 mosaicism may explain the much less frequent paternal origin of T21 DS than maternal. The mechanisms underlying the DS cases, where the extra chromosome 21 does originate from the father, remains unknown and further studies in this respect are required.